Mechanisms of Generating the Arabic Term - Hussein, Najat Amhamad (Arab Journal for Sciences and Research Publishing, 2019)
The discussion of the term issue is a complex subject that requires a lot of effort and time. It has provoked controversy among the various researchers for which they will try to solve these problems. In fact, terminology is the key to science, and we can never discover a science and its logic if we do not master its terminology. As a result of the explosion of knowledge in the world on the various fields of science, we find that the Arabic language is forced to keep pace with this scientific development and this wealth of terminology. This will only be achieved with the investment of specialists in this language by creating terminologies to name the scientific concepts that come from the West every day. For this, we will try in this study to address the subject of the creation of the Arabic term and the mechanisms to introduce it into the dictionary for all that is derivation, sculpture, translation, Arabization and renaissance of heritage. In addition, demonstrate the ability of the dictionary of linguistics in the unification of the latter between Arab scholars and attempt to eliminate the confusion in the dictionary and gaps that have been neglected by the Arab Organization.
Keywords: Terminology; Mechanisms for Generating Arabic Terminology; Unified Dictionary of Linguistic Terms; Derivation; Coinization; Translation